Desenvolvimento e caracterização de micropartículas de amido reticuladas com agente fosfatado e avaliação da adsorção do azul de metileno - Bandeira, Estela Iara (2016)
Starch has properties that make it one of the most studied biopolymers today. It is biodegradable, biocompatible, stable and non-toxic. This work has synthesis of starch and tapioca microparticles, through chemical modification by crosslinking with sodium tripolyphosphate agent in concentrations 7.5 and 15% (m / m). The amylose content was measured for starch and commercial cassava starch at 21.8% and 28.6%, respectively. According to the solubility index, processing in basic medium does not change the solubility of the material, but the addition of crosslinking agent increases this index, which changed from 12.8% for the control unprocessed, to 22.4% for the A5R15 sample. Soluble starch-based materials had a significant increase in the crosslinking density by increasing the concentration of crosslinker, from 1.4 in A5R7,5 sample, to 1.9 in A5R15. The cassava starch-based materials exhibited an opposite behavior: to increase the concentration of crosslinker crosslinking density decreased significantly in F5R7.5 from 2.9, to 1.9 in F5R15 sample. The point of zero charge (PZC) shows that below pH 4 the surface is positively charged. The surface area data is between 3,04 and 1,15 m2.g-1. The pore volume between 2.94 and 1.33 cm3.g-1 and pore size around 1.5 nm. The SEM indicates uneven distribution of microparticles, which are smooth, with no ridges. The maximum adsorption capacity of the materials were tested at pH 7.7 and for A5R15 and CA sample, at pH 2, 5, 6 and 9. It is noted that the processing in basic medium reduces the adsorption capacity of CA and CF in respect fo A and F. The adsorption in A5R15 sample has great dependency on the pH, reaching a value of 587 μg.g-1 in pH 7.7. The samples A5R15 and F5R7,5 adsorbed similar amounts, according to the statistical analysis, and significantly higher than their respective controls and showed lower desorption, indicating that the modification process was effective to control the release of methylene blue. The infrared spectra not show the characteristic bands of the phosphate bonds to the material formed, however, developments in hydroxyl characteristic band suggest modification in the way this group was linked after the reaction. After adsorption, the infrared spectra show different format in the band of hydroxyl. PCA analysis shows that the greatest changes observed in the IR spectra are observed in the region of 3500 cm-1. Thermal analysis showed three thermal events related to dehydration and material degradation. It is observed that the processing increases the temperature to the first mass loss, fixed at 12%, but not observed increased stability due to the presence of crosslinker or process.